Answer:
Step-by-step explanation:
You can start this in may ways but let's start by isolating one of the parenthesis:
x (x² - 5) = - (x - 3)
x³ - 5x = -x + 3 (here I multiplied x for what's inside the parenthesis and the "minus" signal by the other parenthesis which was (x - 3))
x³ - 5x + x = 3
x³ -4x = 3
x³ -4x -3 = 0 (now this right here is a "depressed cubic equation" and it's one of the toughest sit of all time, so good luck with that, you might wanna take a look at this:
ytb/watch?v=rNDy2ZFvG1E
or maybe I'm doing something wrong and it's simpler than that, but whaterver...)
We know: The sum of the measures of the angles of a triangle is equal 180°.
We have: m∠A =65°, m∠B = (3x - 10)° and m∠C = (2x)°.
The equation:
65 + (3x - 10) + 2x = 180
(3x + 2x) + (65 - 10) = 180
5x + 55 = 180 <em>subtract 55 from both sides</em>
5x = 125 <em>divide both sides by 5</em>
x = 25
m∠B = (3x - 10)° → m∠B = (3 · 25 - 10)° = (75 - 10)° = 65°
m∠C = (2x)° → m∠C = (2 · 25)° = 50°
<h3>Answer: x = 25, m∠B = 65°, m∠C = 50°</h3>
124 sq in...................
11: 4,874 > 4,784 > 4,687
12: 8.09 > 8.057 > 8.023
13: 15.820 > 15.280 > 15.000
14: 43,628 > 40,628 > 34,628
15: 395.050 > 395.009 > 395.005
The picture isn't very clear